Degrees of development: how geographic latitude sets the pace of industrialization and demographic change - Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2008)
Successful economic development is usually characterized by two salient phenomena: industrialization and demographic transition. Chronologically both events happen so closely to each other that historians and economists alike suspect that they are interrelated. This paper develops a theory for their interaction with a special emphasis on the different pattern and pace of transition in cross-country comparison. For that purpose it rationalizes why a population grows at high rates at geographic locations of high extrinsic mortality. This mechanism is then used to explain why both demographic transition and structural change proceed at slower speed in countries of low absolute latitudes. It is also shown that at tropical locations the pace of transition can be so slow that it sometimes looks like as if societies got stuck in the midst of the process.
Keywords: J10; J13; O11; O12; 330; Industrialization; Structural Change; Demographic Transition; Geography; Health; Cross-Country Divergence; Entwicklung; Industrialisierung; Drei-Sektoren-Hypothese; Demographischer Übergang; Geographie; Bevölkerungsökonomie; Theorie; Welt